Giant mature cystic teratoma of the ovary mimicking a 36-week pregnancy in a 14-year-old female - Aher, Kalyani Dnyaneshwar; Gadhire, Minakshi; Bhosle, Archana; Agarwal, Nishi (International Journal of Research in Medical Sciences, 2025)
A dermoid cyst is a mature cystic teratoma, most common benign germ cell tumor of the ovary. It arises from totipotent germ cells and can contain well-differentiated tissues from all three germ layers. It is one of the most common benign ovarian neoplasms, occurring in a wide range of sizes. Early diagnosis is essential to prevent potential complications such as torsion, rupture, internal haemorrhage or malignant transformation. Most commonly seen in reproductive age group (20-40 years). Large mature cystic teratoma of ovary exceeding 10cm is extremely rare teratoma. Here we are presenting the case of giant mature cystic teratoma of ovary in 14-year adolescent female, which was mimicking 36weeks pregnancy. Patient had complaints of abdominal distension with decrease appetite and weakness since 2months. On per abdominal examinations there was a lump, which was mimicking 36weeks pregnancy. Which was managed with exploratory laparotomy and left salpingo-oophorectomy and kept her on regular follow up.